2007
DOI: 10.1099/vir.0.83138-0
|View full text |Cite
|
Sign up to set email alerts
|

A cucumber mosaic virus mutant lacking the 2b counter-defence protein gene provides protection against wild-type strains

Abstract: Several plant virus mutants, in which genes encoding silencing suppressor proteins have been deleted, are known to induce systemic or localized RNA silencing against themselves and other RNA molecules containing homologous sequences. Thus, it is thought that many cases of cross-protection, in which infection with a mild or asymptomatic virus mutant protects plants against challenge infection with closely related virulent viruses, can be explained by RNA silencing. We found that a cucumber mosaic virus (CMV) mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 58 publications
6
53
0
Order By: Relevance
“…Although CMVD2b protected to some extent against subsequent infection with Fny-CMV and another CMV strain, there was no indication that this mutant induced a strong, systemic silencing signal (Ziebell et al, 2007). In situ hybridization showed that, although both strains occurred in doubly infected leaves, they did not co-infect the same cells (Ziebell et al, 2007). Such spatial separation (exclusion) has been described for mixed infections between several virus strains (Dietrich et al, 2007;Hull & Plaskitt, 1970;Takahashi et al, 2007;Takeshita et al, 2004).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Although CMVD2b protected to some extent against subsequent infection with Fny-CMV and another CMV strain, there was no indication that this mutant induced a strong, systemic silencing signal (Ziebell et al, 2007). In situ hybridization showed that, although both strains occurred in doubly infected leaves, they did not co-infect the same cells (Ziebell et al, 2007). Such spatial separation (exclusion) has been described for mixed infections between several virus strains (Dietrich et al, 2007;Hull & Plaskitt, 1970;Takahashi et al, 2007;Takeshita et al, 2004).…”
mentioning
confidence: 89%
“…1, row 1, column 2), whereas Fny-CMV caused severe stunting, crinkling and deformation of the youngest plant tissue, resulting in a compact appearance (Fig. 1, row 1, column 4) (Lewsey et al, 2009;Ziebell et al, 2007). FnyCMVD2b was able to provide some cross-protection Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations